2018
DOI: 10.1007/s00425-018-2841-x
|View full text |Cite
|
Sign up to set email alerts
|

The complete plastome of macaw palm [Acrocomia aculeata (Jacq.) Lodd. ex Mart.] and extensive molecular analyses of the evolution of plastid genes in Arecaceae

Abstract: The plastome of macaw palm was sequenced allowing analyses of evolution and molecular markers. Additionally, we demonstrated that more than half of plastid protein-coding genes in Arecaceae underwent positive selection. Macaw palm is a native species from tropical and subtropical Americas. It shows high production of oil per hectare reaching up to 70% of oil content in fruits and an interesting plasticity to grow in different ecosystems. Its domestication and breeding are still in the beginning, which makes th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
32
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 97 publications
8
32
1
Order By: Relevance
“…In the present study, SSRs were mainly localized in intergenic regions and in the LSC. This finding is in agreement with previous results for species belonging to Solanaceae, Poaceae, and Arecaceae [ 5 , 30 , 54 , 55 ]; indeed, the low number of SSRs within IRs is due to its duplicative nature that implies copy-correction activity [ 54 ]. Mono-(p1), di-(p2), and trinucleotide (p3) SSR types were detected in all genotypes under investigation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, SSRs were mainly localized in intergenic regions and in the LSC. This finding is in agreement with previous results for species belonging to Solanaceae, Poaceae, and Arecaceae [ 5 , 30 , 54 , 55 ]; indeed, the low number of SSRs within IRs is due to its duplicative nature that implies copy-correction activity [ 54 ]. Mono-(p1), di-(p2), and trinucleotide (p3) SSR types were detected in all genotypes under investigation.…”
Section: Discussionsupporting
confidence: 93%
“…In particular, SNPs present in psbA and atpI were specific for the C B complex, whereas SNPs in atpB allowed discrimination among species belonging to the C A complex. The use of SSRs in intergenic regions as molecular markers was widely suggested, since these regions evolve faster than coding sequences [ 31 , 55 ]. Among them, we identified the variation in the atpB–rbcL region, already reported by Walsh and Hoot [ 20 ], that elucidated relationships between Capsicum spp., thereby contributing to their taxonomic grouping.…”
Section: Discussionmentioning
confidence: 99%
“…Because the NDH monomer is sensitive to high light intensity, we deduced that the genes encoded NAD(P)H dehydrogenase might have changed drastically to develop new functions for stress resistance 45 , 46 . Previous research reported that genes belong to subunits of cytochrome were under positive selection in some species 47 , 48 , we therefore inferred that petL for cytochrome b6/f complex subunit proteins may have a high evolution rate in the cp genome of F. luojishanense . The gene rpoC2 was associated with PPR7 protein, we thus speculated it may have coevolved with nuclear genes 49 .…”
Section: Discussionmentioning
confidence: 76%
“…sphegodes with few differences: ccs A (5 sites), atp A (3 sites), psa B (2 sites), rps 14 (2 sites), atp F (2 sites) ( S2 Table ) which suggest a general conservation of the RNA editing mechanism within Ophrys but also that RNA editing evolution accumulated enough differences to differentiate two Ophrys species. A previous study has also found that the number of RNA editing sites predicted for protein-coding genes in orchids species is high in comparison with other monocots [ 51 ].Likelihood ratio test between a null model and an alternative model carried out following [ 52 ] shows that 24 genes are under positive selection ( S3 Table ); overall, the most divergent genes have the stronger signatures of positive selection ( S2 Fig ). In details, the positively selected genes were involved in different essential functions such as photosynthesis, PSII ( psb A, psb B, psb E, psb H, psb M, psbN genes), large subunits of rubisco ( rbc L), ATP synthase ( atp I gene), cytochrome b6f ( pet B gene), subunits of RNA polymerase ( rpo A, rpo B, rpo C1, rpo C2 genes), RNA maturation ( mat K gene), ribosomal proteins ( rpl 20, rpl 22, rpl 32, rpl 33, rps 12, rps 19 genes), fatty acid biosynthesis ( acc D gene), cytochrome biosynthesis ( ccs A gene), import of protein in the plastid ( ycf 1 gene), and unknown function ( ycf 2 gene).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, and as already suggested for other monocots as Arecaceae, many tropical orchid species grow as epiphytes in tropical forests and are shade adapted. The transition to the terrestrial habitus of all temperate orchid lineages (as Ophrys ) may have promoted a new selective pressure for improving the photosynthesis efficiency under the new terrestrial ecological conditions [ 52 ].…”
Section: Resultsmentioning
confidence: 99%